2006
DOI: 10.1194/jlr.r500014-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Thematic review series: The Pathogenesis of Atherosclerosis. An interpretive history of the cholesterol controversy, part IV: The 1984 Coronary Primary Prevention Trial ends it—almost

Abstract: As of the early 1980s, despite the wealth of evidence from experimental animal models, the extensive epidemiologic evidence, the powerful genetic evidence, and the strongly suggestive clinical intervention trial results, most clinicians still remained unpersuaded regarding the relevance of the lipid hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 36 publications
(24 reference statements)
2
21
0
2
Order By: Relevance
“…Throughout this series of reviews (1)(2)(3)(4) and in an earlier analysis of the controversy (66), we have identified a num- Fig. 4.…”
Section: Why Did the Cholesterol Controversy Last So Long?mentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout this series of reviews (1)(2)(3)(4) and in an earlier analysis of the controversy (66), we have identified a num- Fig. 4.…”
Section: Why Did the Cholesterol Controversy Last So Long?mentioning
confidence: 99%
“…The first four reviews in this series (1)(2)(3)(4) chronicled the several lines of evidence that supported the lipid hypothesis, including the dietary intervention trials in the 1960s. By 1970, many leaders in atherosclerosis research were firmly convinced that cholesterol lowering would work.…”
mentioning
confidence: 99%
“…In spite of the controversy about the role of cholesterol in the mechanisms underlying the pathogenesis of atherosclerosis, there is still consistent evidence that oxidatively modified LDL plays a key role (1)(2)(3)(4)(5). A large number of studies gave rise to the oxidative hypothesis of atherosclerosis, in which the oxidation of LDL represents the critical point.…”
Section: Introductionmentioning
confidence: 99%
“…(14 yes; 0 no). Although a vote does not constitute scientifi c proof, this 1984 consensus was infl uential in the US Food and Drug Administration's decision to justify approval of cholesterol-lowering therapy without requiring manufacturers to submit at the time of application clinical trial data demonstrating effi cacy in lowering serious CVD events [6]. Many panel members (like their European colleagues) regarded CVD as a dietinduced disease caused by imbalanced food energy.…”
Section: An Irrational Surrogate End Pointmentioning
confidence: 97%
“…The situation recalled by Steinberg [6] was that "The National Institutes of Health (NIH) realized that launching a national program to treat high blood cholesterol levels would be enormously complex and expensive. They could not justify that expense without fi rst having iron-clad proof that treatment would work".…”
Section: An Irrational Surrogate End Pointmentioning
confidence: 99%